Semiconductor TiO2 thin film as an electrolyte for fuel cells. Issue 28 (28th June 2019) - Dong, Wenjing; Tong, Yuzhu; Zhu, Bin; Xiao, Haibo; Wei, Lili; Huang, Chao; Wang, Baoyuan; Wang, Xunying; Kim, Jung-Sik; Wang, Hao
Abstract : An SOFC using semiconductor TiO2 thin film as an electrolyte was designed using the energy band theory to prevent short-circuiting problem. Abstract : Electrolyte layer, made up of an ionic conductor with ignorable electronic conductivity, plays vital roles in transporting ions as well as blocking electron passage in electrochemical devices like a solid oxide fuel cell (SOFC). The electronic conductivity of the electrolyte has been always blamed for bringing in the short-circuiting problem. In this study, however, we demonstrate that the dominant issue is not the electronic conductivity of electrolytes but the energy band diagram of the device. Using a semiconductor TiO2 thin film as an electrolyte, we present a novel design of fuel cell devices from the perspective of the energy band structure and alignment. A TiO2 thin film was fabricated by a mass-productive spin coating method. An OCV of 1.1 V and maximum power output of 364 mW cm −2 at 550 °C were achieved, which proves that TiO2 plays the role of an electrolyte with sufficient ionic transportation while no electronic short-circuiting problem occurs. The online intercalation of Li into TiO2 enables the creation of more oxygen vacancies. Additionally, proton incorporation and conducting mechanisms in TiO2 have been verified and discussed. This work provides a new method for suppressing the electronic conductivity of electrolytes as well as developing functional electrolytes from a well-known semiconductor for advanced low-temperature SOFCs.